Analisis Spasial Deforestasi dan Degradasi Hutan di Suaka Margasatwa Kerumutan Provinsi Riau - Dariono Dariono; Yusni Ikhwan Siregar; Nofrizal Nofrizal (Dinamika Lingkungan Indonesia, 2018)
The existence of forests continues to decline in terms of quantity (breadth) and quality through the process of deforestation and forest degradation. Deforestation and forest degradation have an impact on the destruction of ecosystems in the region and reduced forested areas that lead to less optimal functioning of areas as conservation areas. This study aims to determine the rate and rate of deforestation and forest degradation as well as the source of threats in the Kerumutan Wildlife Reserve area. The analytical method used by land cover change with stages: satellite image cutting, classification, groundcheck and analysis of deforestation rate and forest degradation. Classification uses visual interpretation techniques (on screen digitize). Factors affecting deforestation and forest degradation were analyzed by logistic regression. The results show that for 20 years (1996-2016) there has been deforestation of 2,879.73 hectares (0.15% per year) and forest degradation of 15,604.92 hectares (0.83% per year). Deforestation and forest degradation in SM Kerumutan is influenced by six driving factors such as population density, forest distance from road, forest distance from river, forest distance from settlement, forest distance from agricultural land and forest distance from industrial plantation forest.